2019
DOI: 10.1007/978-3-030-30754-7_5
|View full text |Cite
|
Sign up to set email alerts
|

A Database for Face Presentation Attack Using Wax Figure Faces

Abstract: Compared to 2D face presentation attacks (e.g. printed photos and video replays), 3D type attacks are more challenging to face recognition systems (FRS) by presenting 3D characteristics or materials similar to real faces. Existing 3D face spoofing databases, however, mostly based on 3D masks, are restricted to small data size or poor authenticity due to the production difficulty and high cost. In this work, we introduce the first wax figure face database, WFFD, as one type of super-realistic 3D presentation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For example, 3D facial biometrics was introduced to overcome the limitations of 2D face scanning biometrics, as mere images were able to spoof them. But still, those systems were still vulnerable to 3D face model based counterfeiting attacks [66]. As a result, researchers from this domain have not only been attempting to improve the existing systems but also are constantly looking for more reliable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 3D facial biometrics was introduced to overcome the limitations of 2D face scanning biometrics, as mere images were able to spoof them. But still, those systems were still vulnerable to 3D face model based counterfeiting attacks [66]. As a result, researchers from this domain have not only been attempting to improve the existing systems but also are constantly looking for more reliable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…To further demonstrate the effectiveness of the second contribution of this article i.e., the development of a robust algorithm across different attacks, additional experiments are performed on the existing benchmark databases in the VIS spectrum. The performance of the proposed algorithm is evaluated on the CASIA-Face Anti-Spoofing Database (FASD) (Zhang et al, 2012), Replay-Attack (Chingovska et al, 2012), MSU-MFSD (Wen et al, 2015), 3D Mask Attack Database (3DMAD) (Erdogmus and Marcel, 2013), MSU USSA database (Patel et al, 2016), WMCA , SiW-M (Liu et al, 2019b), Silicone Mask Attack Database (SMAD) (Manjani et al, 2017), and 3D wax figure face database (WFFD) (Jia et al, 2019). These databases cover a wide spectrum of attacks such as print, photo, a replay of video, 3D hard resin masks, and the most challenging silicone mask.…”
Section: Experiments On Existing Vis Spectrum Databasesmentioning
confidence: 99%
“…Recently, a new modality of 3D attack is highlighted where wax figure faces are used as a possible adversary on face recognition systems (Jia et al, 2019). The authors have shown that state-of-the-art face recognition algorithms such as OpenFace (Amos et al, 2016) and Face++ 5 are vulnerable to wax figure faces.…”
Section: Experiments On Existing Vis Spectrum Databasesmentioning
confidence: 99%
“…Most 3D PAD datasets are based on wearable hard-resin or silicone masks. Wax figure face databases were reported in [ 34 , 35 ] for super-realistic 3D presentation attack research. For the work presented in this paper, a database has been locally collected as none of the public databases include the type of challenge–response, artefacts and device formats, which are investigated in this paper.…”
Section: State Of the Artmentioning
confidence: 99%